Development of sustainable comfortable socks from recycled leno waste - Akhtar, Shahan; Ahmad, Faheem; Nawab, Yasir; Rasheed, Abher; Ahmad, Sheraz; Azam, Farooq (Journal of engineered fibers and fabrics, 2024)
Society’s growing concern for the environment has led to an increased emphasis on greener products and processes. While societies are becoming more accepting of this change, there are still significant challenges regarding the esthetic aspect of environmentally friendly products. Textiles, which are essential for providing cover and esthetics, contribute to environmental pollution through waste production. Currently, the production of hard waste yarn, a textile intermediate product, utilizes the OE (open-end) spinning method to make use of textile waste. However, this approach has limitations in terms of quality, as it results in yarn with low abrasion resistance, higher pilling, and poor physical appearance of garments. Consequently, consumers are less satisfied with these sustainable yarns, hindering their widespread use. This study focused on preparing ring-spun yarn from recovered fibers of leno waste and subsequently producing knitted fabrics from these yarns. The properties of these fabrics were analyzed and compared with fabrics made from 100% virgin ring spun yarn. The results revealed that the fiber reclaimed from leno waste had a higher content of short fibers. The yarn produced from these fibers exhibited higher imperfections, unevenness, and reduced strength as the percentage of reclaimed fibers increased. Socks made with an increasing percentage of leno waste showed higher thermal resistance. However, as the yarn became finer, the thermal resistance of the socks decreased. On the other hand, the air permeability of the socks increased with a finer yarn count. Overall, the moisture management of all samples was good, with coarser yarns exhibiting better moisture management in socks. An ANOVA approach was used to statistically evaluate the properties of the yarn and fabric. The conclusion drawn from the study was that these recycled yarns can be effectively utilized in the socks and denim industry without compromising quality.